Caecal volvulus: A report of three paediatrics cases - Benmassaoud Zineb; Fatoumata Binta Baldé; Othmane Alaoui; Abdelhalim Mahmoudi; Khalid Khattala; Youssef Bouabdallah (Wolters Kluwer Medknow Publications, 2023)
Caecal volvulus is favoured by the lack of caecal adhesion and intestinal malrotation. According to the per operation findings, the treatment consists of a de-rotation with or without cecopexy. We present the three cases of caecum volvulus in children and discuss our management. Case 1: 11-year-old girl admitted for caecal volvulus in an acute occlusive syndrome picture. There was caecal volvulus and atresia of the volvulated area. We performed resection and end-to-end anastomosis. Good evolution. Case 2: 6-year-old girl admitted for caecal volvulus in an acute occlusive syndrome picture. We performed caecopexy at the right parietal-colic gutter by three interrupted stitches. Good evolution. Case 3: 6-year-old girl admitted for caecal volvulus in an acute sub-occlusive syndrome picture with hypovolemic choc stage. There were suffering areas and necrosis of the caecum, a part of the ascending colon and iléal loops. We resected the gangrene part of the digest if tract and performed end-to-end ileocolic anastomosis. Good evolution. Caecal volvulus is rare. In our series, a patient had an ultrasound diagnosis. The diagnosis of caecum volvulus was made by computed tomography scan to the second one. The third patient had a perioperative diagnosis which is frequently reported in the literature. Management varies from the simple de-rotation with appendectomy to caecopexy. Caecal volvulus is a therapeutic emergency because the risk of necrosis and perforation is obvious. With proper support, the overall evolution is good.